International spectrum management regime: is gridlock blocking flexible spectrum property rights?. Issue 2 (13th March 2017) - El-Moghazi, Mohamed; Whalley, Jason; Irvine, James
Abstract : Purpose: This paper aims to examine the influence of the international spectrum management regime on the introduction of flexibility in the national allocation of radiocommunication services. This is achieved through focusing on the main elements of the international regime. Design/methodology/approach: A qualitative inductive methodology is adopted that examines the different elements of the international radiocommunication service allocation framework. Data are drawn from 66 semi-structured interviews with key stakeholders who are actively involved in International Telecommunication Union Radiocommunication Sector discussions. Findings: The international radio regulations (RR) are perceived to be more of a framework for harmonisation that does not constrain the flexibility of countries. Countries are only restricted on their borders with their neighbours, and flexibility is already facilitated through a range of different measures. Moreover, several elements of the RR can be used to achieve both, i.e. to promote flexibility and to restrict the decisions of others. Practical implications: The international spectrum management regime is not one of the reasons for the unsuccessful practical application of the flexible spectrum property rights concept. This suggests the need for reviewing whether there still is a need for such a concept given the increasing importance of global harmonisation and economies of scales. Originality/value: This paper sheds light on spectrum property rights from the perspective of the international spectrum management regime. Such a perspective is largely overlooked in the on-going current debate.